Experiências sociais sobre as políticas de inserção vividas por estudantes no departamento de educação campus Guanambi da Universidade do Estado da Bahia: acesso, permanência e das ações afirmativas - Fausta Porto Couto (2021)
This investigation aimed to understand how students are reading and interpreting public policies of social inclusion of affirmative actions, permanence and integration that imply in the construction of their individuation within of a public university. This research is supported by the assumptions of Dubet (1994) and Martuccelli (2007), regarding the relations between subject and society, which present the individual as a questioner of their social roles and builder of strategies in the interaction actions that their time and space may give rise to. The research findings were analyzed from some concepts: social experience and its logic, from Dubet; evidence, supports and papers, from Martuccelli; and the concept of affirmative action as a public policy, systematizing the information from the exploratory questionnaire (231 students) and episodic narrative interviews of 23 students of different age groups, gender, race and class of the four undergraduate courses from the Department of Education - DEDC Campus XII of the State University of Bahia - UNEB. The students' evaluation of the policies promoted by UNEB and the differences identified in their experiences show the need for strengthening ethnic-racial identities and belongings. They also demonstrate that structural racism is rooted in everyday relationships, as well as stigmas, sexism and religious prejudice. It is also worth mentioning, in this sense, that, for affirmative actions, it is necessary to contextualize the concept of race beyond the quotas, just as, in student assistance, actions need to be thought of without meritocracy criteria. To enter university through racial or social quotas does not diminish the facing of hardships (MARTUCELLI, 2006) whether meritocratic or structural, because it will demand from the individual a greater effort, since there is no support from the State for this. Although studying is a right for those who have children, work, family or have already decided to study after 30 years old, there are challenges in trying to reconcile so many adverse situations. The students’ interpretations about social inclusion policies refer to their daily interactions within the university structures and other social mechanisms, considering the supports that facilitate or hinder their permanence, access and/or integration.